Kinase Inhibition as Treatment for Acute and Chronic Graft-Versus-Host Disease - Braun, Lukas M.; Zeiser, Robert (Frontiers in Immunology, 2021)
Allogeneic hematopoietic stem cell transplantation (allo-HCT) is a potentially curative therapy for patients suffering from hematological malignancies via the donor immune system driven graft-versus-leukemia effect. However, the therapy is mainly limited by severe acute and chronic graft-versus-host disease (GvHD), both being life-threatening complications after allo-HCT. GvHD develops when donor T cells do not only recognize remaining tumor cells as foreign, but also the recipient’s tissue, leading to a severe inflammatory disease. Typical GvHD target organs include the skin, liver and intestinal tract. Currently all approved strategies for GvHD treatment are immunosuppressive therapies, with the first-line therapy being glucocorticoids. However, therapeutic options for glucocorticoid-refractory patients are still limited. Novel therapeutic approaches, which reduce GvHD severity while preserving GvL activity, are urgently needed. Targeting kinase activity with small molecule inhibitors has shown promising results in preclinical animal models and clinical trials. Well-studied kinase targets in GvHD include Rho-associated coiled-coil-containing kinase 2 (ROCK2), spleen tyrosine kinase (SYK), Bruton’s tyrosine kinase (BTK) and interleukin-2-inducible T-cell kinase (ITK) to control B- and T-cell activation in acute and chronic GvHD. Janus Kinase 1 (JAK1) and 2 (JAK2) are among the most intensively studies kinases in GvHD due to their importance in cytokine production and inflammatory cell activation and migration. Here, we discuss the role of kinase inhibition as novel treatment strategies for acute and chronic GvHD after allo-HCT.